Concomitant Infections With Canine Parvovirus Type 2 and Intracellular Tick-Borne Pathogens in Two Puppy Dogs - Urbani, Lorenza; Tirolo, Alessandro; Balboni, Andrea; Troia, Roberta; Dondi, Francesco; Battilani, Mara (Frontiers in Veterinary Science, 2022)
In this report the concomitant infection with canine parvovirus type 2 (CPV-2), Hepatozoon canis and Ehrlichia canis in two puppy dogs from Southern Italy is described. Dogs were referred to a veterinary university hospital for the acute onset of lethargy and gastrointestinal signs. A complete clinical and clinicopathological evaluation was carried out and the multiple infection was confirmed by microscopic detection of inclusion bodies in peripheral blood smear, rapid immunoenzymatic tests, indirect fluorescent antibody tests, and molecular assays. Sequence analysis revealed that the CPV-2 identified belonged to the 2c variant and had amino acid residues in the predicted VP2 protein typical of “Asian-like” strains widespread in Asia and occasionally reported in Romania, Nigeria and Italy, particularly in the region of Sicily. Numerous monocytes were infected by both H. canis gamonts and E. canis morulae, suggesting that this co-infection is not accidental and that E. canis preferably infects those cells parasitized by H. canis. The clinical presentation of these animals was severe but supportive cares associated with early etiological therapy allowed a good prognosis. Movement of puppies from geographic areas where vector-borne pathogens are endemic must be carefully evaluated and core vaccinations and ectoparasite prevention treatments must be rigorously adopted.